Peran Wakaf Produktif dalam Pemberdayaan Ekonomi Umat: Studi pada Model Pengelolaan Berbasis Maqashid Syariah - Rupita, Nanda Ega; Mawardi, Mawardi (Al-Muzdahir : Jurnal Ekonomi Syariah, 2025)
This study aims to explore the role of productive Waqf in the economic empowerment of the Ummah through the approach of maqashid Sharia, namely the principles of protection of religion, soul, intellect, heredity, and property. Using qualitative methods based on literature studies, this study highlights the great potential of productive Waqf in supporting various strategic sectors such as education, health, economy, and infrastructure. The results show that professional management of waqf assets can generate sustainable benefits, such as financing social programs, developing MSMEs, and improving the quality of human resources. The main challenge in this management is the low literacy of waqf in the community as well as regulatory constraints that have not been fully supported. Nonetheless, the principles of maqashid Sharia provide a solid foundation to ensure that Waqf management is not only oriented towards economic benefits, but also creates significant social impacts. In conclusion, productive Waqf plays a strategic role as an instrument of Islamic philanthropy that not only supports poverty alleviation but also encourages people's economic independence holistically and sustainably.